Antimicrobial and Anti-Quorum Sensing Activities of Phlorotannins From Seaweed (Hizikia fusiforme) - Tang, Jiali; Wang, Wenqian; Chu, Weihua (Frontiers in Cellular and Infection Microbiology, 2020)
Multidrug-resistant bacteria (MDR) are becoming a global health problem, and scientists are continuously investigating new strategies to fight against MDR. Seaweeds are an important source of biological compounds and can serve as natural sources for bacterial infection control. This study evaluated the antimicrobial and anti-quorum sensing (QS) activities of phlorotannins from Hizikia fusiforme. The phlorotannins exhibited antimicrobial activity against selected bacterial pathogens and inhibited QS activity of the reporter strain Chromobacterium violaceum 12472 by inhibiting purple pigment production. Phlorotannins can decrease the bacterial motility, reduce the production of extracellular protease, hemolysin, and pyocyanin and inhibit biofilm formation of Pseudomonas aeruginosa. In vivo studies showed that phlorotannins can reduce P. aeruginosa inflicted mortality in Caenorhabditis elegans. This study shows that phlorotannins from H. fusiforme have certain antimicrobial and anti-quorum sensing activities and have the potential to control bacterial infection for pharmaceutical usage.